Studi kasus: Canine chronic ulcerative stomatitis pada anjing Pomeranian - Zumara Mufida Hidayati; I Nyoman Suartha; I Gede Soma (Universitas Sulawesi Barat, 2021)
Chronic inflammation of the oral cavity accompanied by ulcers called Canine Chronic Ulcerative Stomatitis (CCUS). A Pomeranian dog was examined at the Animal Hospital, Faculty of Veterinary Medicine, Udayana University with complaints of decreased appetite and drinking accompanied, in the dog that would not close his mouth. Clinical examination showed that there is bleeding and swelling of the gums and lips, torn sores and ulcer on the lower lip, redness on the edge of the tongue, blackish plaque in almost all of his teeth, halitosis, and enlargement of the mandibular lymph nodes, and routine hematological examination showed a normochromic and normocytic anemia, elevated monocyte levels, and neutrophilia, so dogs were diagnosed with CCUS. Treatment using Amoxicillin, Meloxicam, Vitamin C, Ferrous Sulfate, and fluid therapy using NaCl initially gave quite good results, but the dog died on the sixth day after therapy which possibly due to severe malnutrition and anemia.